If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(y+2)=5y
We move all terms to the left:
6(y+2)-(5y)=0
We add all the numbers together, and all the variables
-5y+6(y+2)=0
We multiply parentheses
-5y+6y+12=0
We add all the numbers together, and all the variables
y+12=0
We move all terms containing y to the left, all other terms to the right
y=-12
| 7y-1=7y-y | | 8=4(b−15) | | 2m—14=60 | | 2/3x+1/3x=3 | | 2(k+1)-(3+8k)=-7k | | 3/m-6=1/m | | n+3n=41 | | |3x+8|=9 | | 1-2x=5+2x | | 6/25=2x+10/15 | | x2=25-1 | | 2x2-2=48 | | -16-6x=-2(-1+4x) | | x+.12x=592.48 | | 2x3+4=20 | | 6p+7=9-5p | | (2x+10)=(9x-11) | | 5=5x+27M | | 1/2(8x-10)=1/5(25x-20) | | -16-6n=2(1+4n) | | x+(3x)=300 | | 400=72+4t | | 3x+8-4x+10=8 | | 5(t+6)-2(7t-5)=-10(t-2)+8 | | 40-5x=6 | | 2k+6=42-4k | | -3(2b-2)=4 | | 28=-4(3r+5 | | X^2+12x=492 | | 4x-7x=55 | | 8x+36=180-4x | | x/9+16=2” |